A channel assignment scheme for MIMO on concentric-hexagon-based multi-channel wireless networks. (17th November 2020) - Leu, Fang-Yie; Susanto, Heru; Tsai, Kun-Lin; Ko, Chia-Yin
In a wireless network, multiple channels can increase network capacity. However, it causes other problems, e.g., multi-channel hidden terminal problem and the issue about how to allocate channels to wireless nodes. Basically, a well-defined channel assignment can avoid radio interference and improve transmission performance. Therefore, in this study, we proposed a multiple channel assignment scheme, called concentric-hexagon-oriented multi-channel assignment (CHOMA for short), in which all deployed eNBs are organized as concentric-hexagon (C-hexa for short). Available channels are grouped and then allocated to the C-hexas. We also arrange channels allocated to a C-hexa so as to reduce radio interference among its eNBs, consequentially improving the transmission capability and performance of a wireless network. Experimental results show that the CHOMA is really an interference-free scheme, no matter whether the target system is a network with SISO, SIMO, MISO or MIMO stations.